Three essays on the economic effects of combat related post-traumatic stress disorder on U.S. veterans - Lee, Kelly M., author; Pena, Anita, advisor; Zahran, Sammy, committee member; Mushinski, David, committee member; Stallones, Lorann, committee member (Colorado State University. Libraries, 2022)
Since September 2001, approximately 2.77 million military service members have served on over 5.4 million deployments (Wenger, 2018) to Iraq and Afghanistan in support of Operation Enduring Freedom (OEF), Operation Iraqi Freedom (OIF), and Operation New Dawn (OND). Soldiers returning from these deployments are at risk of experiencing adverse mental health issues, to include post-traumatic stress disorder (PTSD) and depression. The first-stage of this study examines the relationship between exposure to combat and a diagnosis of PTSD and depression. Then, I explore the effects a diagnosis of PTSD and depression have on the employment and risk-taking behaviors of U.S. service members. Chapter 1 focuses on active duty service members, veterans, and National Guardsmen and Reservists and estimates the effects of combat on their mental health outcomes. I then decompose the effects of combat and examine the effect of differing measures of combat on mental health. These measures include deployment length, exposure to enemy firefight, killing or wounding someone, and exposure to the death or injury of an ally, civilian, or enemy. I find that exposure to combat and several separate combat events leads to higher probabilities of adverse mental health outcomes for military members. Chapter 2 explores the effect a diagnosis of PTSD has on several employment outcomes for U.S. veterans. First, using a standard probit model, I examine the effect of PTSD on four employment outcomes: the probability of employment, the number of hours worked per week (on average), employment sector, and job satisfaction. I find that PTSD is associated with a decreased probability of employment and a decrease in the number of hours worked per week. However, if PTSD is endogenous, then these results will be biased. For example, veterans with PTSD may be perceived by potential employers as being dangerous or incompetent (Hipes & Gemoets, 2019), which could affect the probability of employment. To address this concern, I employ a two-stage estimation approach using exposure to combat as an instrument to minimize the bias in the estimated effect of PTSD on the probability of employment and the number of hours worker per week. I find no significant effect of PTSD on either outcome. Chapter 3 focuses on the relationship between a diagnosis of PTSD and depression and the risk-taking behaviors of service members. Risk-taking behaviors are defined as intentional behaviors that have potential negative consequences or loss and have been found to be positively associated with PTSD. U.S. military personnel returning from deployments are experiencing adverse mental health issues which can lead to an increase in risk-taking behaviors. This increase in risk-taking behaviors can lead to worse economic outcomes for veterans, such as high unemployment rates and decreased earnings. I approach this question from two separate directions. First, I examine the effect a diagnosis of PTSD or depression has on the risk-taking behaviors of U.S. veterans. Second, I examined the association of exposure to combat on risk-taking behaviors using the combat events found to be significant to a diagnosis of PTSD or depression in Chapter 1. I find that PTSD is associated with an increase in the use of nicotine, alcohol, and other substances. As stated above, the broad goal of this research is to improve our understanding of the long-term consequences a diagnosis of combat-related PTSD has on U.S. veterans. Chapter 1 allows me to explore the effect different combat experiences have on the probability of adverse mental health outcomes. While Chapter 1 looks at the direct effects of combat exposure on mental health outcomes, Chapter 2 looks beyond the combat experience and examines the effect a diagnosis of combat-related PTSD has on the employment outcomes of U.S. veterans. Chapter 3 extends the work in the previous chapter by exploring one potential reason for the lower levels of employment found in U.S. veterans by examining the effect PTSD and depression have on the risk-taking behaviors of previously deployed service members.